Coordination between municipalities and local Non-Municipal Public Units (NMPUs) for supporting urban economic development: Theoretical analysis and empirical evidence for the example of universities in Germany - Martin T. W. Rosenfeld; Jana Hinz (Koordination raumwirksamer Politik: Mehr Effizienz und Wirksamkeit von Politik durch abgestimmte Arbeitsteilung, 2015)
In many European cities, policymakers are trying to change the local paths of economic development to head in new directions, e. g. by trying to become a location for Non-Municipal Public Units (NMPUs), like federal special agencies, state museums, military bases, universities or publicly funded research institutes. But as the competencies for such local NMPUs are allocated to higher levels of government, the municipal level has no direct formal institutional responsibilities for influencing their location. Once a NMPU has chosen a certain location, support from the municipality may, however, stabilize the NMPU. There are some categories of NMPUs that should have considerable interest in local conditions, as determined by the municipal level. This paper first theoretically categorizes NMPUs with regard to their importance for the urban economy, with regard to the importance of local conditions for the performance of NMPUs and with regard to their degree of fiscal autonomy. It is shown that universities are one example of NMPUs where the relevance of coordinating activities with the municipalities is fairly high. The benefits of universities for local economic development have often been discussed. From the point of view of universities, their capacity to attract human capital depends on factors which may be influenced by the municipalities. This means that there is a reciprocal relationship between municipalities and universities; coordination by cooperation between the partners could be useful for both - but in practice there is often a lack of cooperation. Information policy is one relevant field for coordination: the city should highlight publicly the advantages of local universities; the universities should highlight the advantages of their city. As information policy is a field for which empirical data is available, the empirical part of the paper presents results from an analysis based on the internet presentations of selected cities and universities. It is shown that in most cities the level of coordination in this field is so far quite low. One possible way to achieve a higher degree of coordination could be to introduce fiscal incentives for cities. – – In zahlreichen europäischen Städten gibt es Versuche, der lokalen Wirtschaftsentwicklung eine neue Richtung zu geben, u. a. durch die Ansiedlung von Nicht-Kommunalen Öffentlichen Einrichtungen (NKOE), z. B. Bundesagenturen, Gerichte, Rechnungshöfe, Landesmuseen oder Universitäten. Allerdings liegen die Kompetenzen für solche NKOE nicht bei den Kommunen, sondern zumeist bei den höheren staatlichen Ebenen. Deshalb haben die Kommunen keinen unmittelbaren Einfluss auf die Ansiedlung von NKOE. Sobald aber eine entsprechende Entscheidung gefallen ist, können die Kommunen die weitere Entwicklung von NKOE begünstigen. Im Beitrag wird zunächst eine Kategorisierung von NKOE durchgeführt, und zwar sowohl gemäß der Bedeutung von NKOE für die lokale Wirtschaftsentwicklung als auch hinsichtlich des Einflusses lokaler Maßnahmen auf die Leistungsfähigkeit von NKOE. Es wird gezeigt, dass Universitäten zu jener Kategorie von NKOE zählen, für die eine Koordination der eigenen Aktivitäten mit jenen der Kommunen besonders wichtig sein dürfte. Die Effekte von Universitäten für die lokale Wirtschaftsentwicklung wurden bereits vielfach diskutiert. Die Fähigkeit der Universitäten, das für ihre Effektivität erforderliche Humankapital zu attrahieren, hängt von verschiedenen lokalen Faktoren ab. Folglich gibt es eine reziproke Beziehung zwischen Kommunen und Universitäten. Eine Koordinierung der jeweiligen Aktivitäten wäre deshalb für beide Seiten von Vorteil. Dies gilt z. B. für den Bereich der Informationspolitik. Eine Kommune sollte nach innen wie nach außen die Vorzüge der örtlichen Universitäten kommunizieren; umgekehrt sollte auch eine Universität die Stärken des lokalen Umfelds deutlich machen. Da für den Bereich der Informationspolitik empirische Daten leicht zugänglich sind, konzentriert sich der empirische Teil des Beitrags auf eine empirische Untersuchung der Internetpräsentationen ausgewählter Städte und Universitäten. Es zeigt sich, dass in den meisten betrachteten Städten die Koordinierung zwischen Kommunen und Universitäten zu wünschen übrig lässt. Eine Verbesserung dieser Situation ließe sich z. B. durch die Einführung finanzieller Anreizmechanismen erreichen.
urn:nbn:de:0156-0778118; hdl:10419/109651; http://econpapers.repec.org/RePEc:zbw:arlfob:4
Keywords: 710; Urban economic growth; coordination of public activities; intergovernmental relations; public research units; universities; Lokale Wirtschaftsentwicklung; Koordination öffentlicher Aktivitäten; Föderalismus und Finanzausgleich; öffentliche Forschungseinrichtungen; Universitäten